2004
DOI: 10.1016/s1743-9191(06)60050-2
|View full text |Cite
|
Sign up to set email alerts
|

CRP in Acute Appendicitis — Is It a Necessary Investigation?

Abstract: We conclude that neither raised nor normal CRP value is helpful in the diagnosis of acute appendicitis. CRP is not a good tool for helping the surgeon make the diagnosis of appendicitis and it should not be measured in suspected appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Therefore, CRP may be useful to differentiate LH from acute appendicitis, but not useful to determine the severity of inflammation. On the contrary, Amalesh et al [19] noted that neither elevated nor normal CRP level was helpful in the diagnosis of acute appendicitis. This result may be due to the pediatric patient population of their study.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, CRP may be useful to differentiate LH from acute appendicitis, but not useful to determine the severity of inflammation. On the contrary, Amalesh et al [19] noted that neither elevated nor normal CRP level was helpful in the diagnosis of acute appendicitis. This result may be due to the pediatric patient population of their study.…”
Section: Discussionmentioning
confidence: 97%
“…The reported predictive values of CRP in appendicitis vary widely: reported sensitivities range from 40% to 99% and specificities from 27% to 90% [17]. Amalesh et al [11] reported that the accuracy of CRP for diagnosing acute appendicitis is low and added that CRP levels are not useful when deciding on surgery. However, Ortega-Deballon et al [5] recently concluded that CRP level is the most useful laboratory parameter in terms of diagnosing acute appendicitis and that CRP levels are strongly correlated with inflammation severity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some investigators have stressed the importance of these blood inflammatory markers in the context of deciding upon discharge or admission for further investigation [5][6][7][8][9][10]. However, some reports show that these inflammatory markers have low diagnostic accuracy in acute appendicitis [11][12][13]. As a result of these disparate results, the importance of WBC counts and CRP levels during the diagnostic stage remains controversial.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] In such condition clinical and laboratory investigations may be the only, cheaper and readily available options for diagnosis. In this study we have tried to compare the difference in the level of serum bilirubin between patients with gangrenous and non-gangrenous appendicitis.…”
mentioning
confidence: 99%